Karakteristik Perahu Sandeq Perangkap Ikan Berbahan Kayu Bulat di Provinsi Sulawesi Barat - Misliah Idrus; Syamsul Asri; Rusman Rusman (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
The Sandeq boat is a type of traditional boat used for fishing and sea transportation by the Mandar people, in the coastal area of ​​West Sulawesi. Round wood is still the main material used in making sandeq boats. The aim of this research is to determine the characteristics of sandeq fishing boats made of wood in the province of West Sulawesi. Determining of the respondent is this research is done by purposive. Analysis method is used: qualitative and quantitative descriptive analysis. The result of the research shows that there were 4 types of sandeq boats used to catch fish, namely the Pangoli types with a length 5-7 meters as much as 55,23 %, Parroppong and Potangga types with a length 7 – 11 meters as much as 41, 91 %, and Pallarung types with a length >11 meters as much as 2,86 %. The four types of sandeq boats used a combination of sails and engines as propulsion. The main construction includes: stripes (lunas), sideboards (palamma boards), ivories (tajo), deck boards (kalandara), katir beams (baratang), and masts (palayarang). The L/B of a sandeq boat average 8.23-11,27 which intends to increase if the length is added to indicate that they are appropriate for high speed boats, while the L/H   ratio of sandeq boats average 7,25-10,30 which tends to increase in length indicates that sandeq boats are lacking in terms of elongation resistance.  The B/H ratio of a sandeq boat average 0,89-0,92 which is relatively low and tends to be the same indicates that the stability of the boat is not good. This study suggests that further research are needed to do advance research on the longitudinal resistance of sandeq boats, as well as more in-depth research on the stability of outrigger boats is required.